African dairy value chain seminar: Comments from participants - International Livestock Research Institute; Technical Centre for Agricultural and Rural Cooperation (International Livestock Research Institute, 2014)
This film shares comments from participants of the African dairy value chain seminar held 21-24 September 2014 in Nairobi, Kenya. The seminar was organized by the Technical Centre for Agricultural and Rural Cooperation (CTA) and ILRI.